Sleeper and the Spindle - Gaiman, Neil; Riddell, Chris (New York Harper, 2015)
On the eve of her wedding, a young queen sets out to rescue a princess from an enchantment. She casts aside her fine wedding clothes, takes her chain mail and her sword, and follows her brave dwarf retainers into the tunnels under the mountain towards the sleeping kingdom. This queen will decide her own future -- and the princess who needs rescuing is not quite what she seems.
Keywords: Snow White (Tale); Sleeping Beauty (Tale); Queens; Princesses; Quests (Expeditions); Search and rescue operations; Fairy tales; Young adult fiction; Fairy tales